2019
DOI: 10.1111/dth.12803
|View full text |Cite
|
Sign up to set email alerts
|

Isotretinoin and candida immunotherapy for recalcitrant warts in solid organ transplant recipients

Abstract: Treatment of recalcitrant warts in solid organ transplant recipients (SOTR) can pose a therapeutic challenge for dermatologists. Successful treatment of recalcitrant warts can serve as secondary prevention for skin cancer in those with chronic immunosuppression. Given the heterogeneity of associated comorbid conditions in SOTR, clinical trials are difficult to conduct in this high‐risk population, therefore, our clinical practice is mostly driven by observed responses from studies in immunocompetent patients o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 15 publications
(17 reference statements)
0
7
0
1
Order By: Relevance
“…Reports of two cases by McDonald et al 7 . and one case by Burton and Sawchuk, 8 also indicated safe and effective treatment of the same entity with isotretinoin, Herold et al 9 . reported two cases of recalcitrant warts in patients with renal impairment following solid organ transplants, one of whom was on renal dialysis, who had successful treatment with isotretinoin 20 mg daily in combination with immunotherapy for Candida .…”
Section: Resultsmentioning
confidence: 96%
“…Reports of two cases by McDonald et al 7 . and one case by Burton and Sawchuk, 8 also indicated safe and effective treatment of the same entity with isotretinoin, Herold et al 9 . reported two cases of recalcitrant warts in patients with renal impairment following solid organ transplants, one of whom was on renal dialysis, who had successful treatment with isotretinoin 20 mg daily in combination with immunotherapy for Candida .…”
Section: Resultsmentioning
confidence: 96%
“…8 In both conditions, viral warts precede the onset of carcinoma. 9 Another relevant factor is the higher prevalence of HPV in samples of squamous cell carcinomas (78%) when compared to basal cell carcinomas (36%) and even normal skin (32%). 8 Nevertheless, the mere evidence of a viral infection is not enough to incur a malignant transformation, because most patients infected with HPV do not develop cancer.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of IFN-alpha-2a (3 million units, three times a week for 2 months) and oral isotretinoin (0.5 mg kg -1 day -1 for 3 months) was found to be highly effective in recalcitrant warts (Yildirim, Inaloz, Baysal, Kesici, & Candir, 2004). Herold, Nielson, and Longo (2019) observed that isotretinoin 20 mg/day in combination with candida immunotherapy 0.2 cc/2 weeks showed a drastic improvement within few weeks in two adult patients with recalcitrant warts.…”
Section: Wartsmentioning
confidence: 99%
“…Herold, Nielson, and Longo () observed that isotretinoin 20 mg/day in combination with candida immunotherapy 0.2 cc/2 weeks showed a drastic improvement within few weeks in two adult patients with recalcitrant warts.…”
Section: Indications Of Low‐dose Isotretinoin In Dermatologymentioning
confidence: 99%